CULTURAL PARTICIPATION AND TOURISTIC VALORISATION OF THE LOCAL CULTURAL HERITAGE - LUCIAN, Marina (Annales Universitatis Apulensis Series Oeconomica, 2015)
Cultural participation has been examined by most studies as a consequence of a complex of socio-demographic factors and less of attitudinal ones. This paper investigates the link between participation in cultural events and attitudes towards cultural and historical heritage within the context of a process of urban regeneration and development of cultural marketing activities. Examining data from two surveys conducted on the same urban population during two consecutive years, we find a significant association between participation in cultural events and several socio-demographic factors, including education and age. We will use several logistic regression models to see the combined influence of socio-demographic factors and the attitude factors towards participation in cultural events. The survey results provide empirical support for the existence of a strong relationship between participation in cultural events and a positive attitude towards the proposals for cultural or tourism valorisation of the regenerated urban spaces.